Productive Efficiency of the European Union Member Countries: An Economic Assessment in Post?Brexit Perspective - Rasheed, Rukhsana; Ishaq, Mazhar Nadeem; Anwar, Rabea (iRASD Journal of Economics, 2022)
This study used a modified Cobb-Douglas production model to estimate and test production input co-efficient for Group 28 (including the U.K), Group 27 (excluding the U.K) and individual European Union member countries by using the data of 31 years from 1990 to 2020. Results indicate that the log-linear C-D production model fits the data very well in terms of capital, male and female labour force elasticities, measuring the return to scale, standard errors and economies of scale for Group as well as for individual member countries. Results showed EU 28, EU 27 and from the list of member countries only United Kingdom, Slovak Republic, Slovenia, Czech Republic, Malta, Cyprus, Poland, Hungary, Estonia, Finland, Germany and Netherland are on increasing return to scale, only France is a constant return to scale (as value 0.99, close to 1) and remaining countries are on decreasing return to scale. The study also finds that the United Kingdom as an individual performing increasing return to scale so U.K separation (Brexit) from EU will not harm the U.K and even EU itself, as EU is on increasing return to scale after including/excluding U.K. Study also finds that EU as a group of 27 member countries exhibits increasing return to scale, which is a symbol for overall EU growth and development and suggestion for East Asian and South Asian countries to make a trading bloc or union like European Union.